2009
DOI: 10.1007/s11240-009-9573-3
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of callogenic capacity in date palm leaf tissues in response to 2,4-D treatment

Abstract: While callogenesis in date palm can be initiated by culturing immature leaf segments on medium containing 2,4-dichlorophenoxyacetic acid (2,4-D), it is difficult to obtain callus from certain genotypes. To better understand the mechanisms of callogenesis in date palm, we studied the developmental events underlying this process at the cellular level. The callogenic capacity of leaf segments depends on the state of cell differentiation. The most callogenic segments were within the leaf elongation zone, required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 30 publications
3
23
0
4
Order By: Relevance
“…In Phoenix dactilyfera, leaf explants showed cellular alterations in the fascicular parenchyma after two days of in vitro culture in the presence of NAA (Gueye et al 2009b) or 2,4-D (Gueye et al 2009a). In leaf TCLs of Bactris gasipaes cultured in the presence of picloram, Steinmacher et al (2007c) observed the first cell divisions after 30 days located near vascular bundles.…”
Section: Discussionmentioning
confidence: 99%
“…In Phoenix dactilyfera, leaf explants showed cellular alterations in the fascicular parenchyma after two days of in vitro culture in the presence of NAA (Gueye et al 2009b) or 2,4-D (Gueye et al 2009a). In leaf TCLs of Bactris gasipaes cultured in the presence of picloram, Steinmacher et al (2007c) observed the first cell divisions after 30 days located near vascular bundles.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional method of date palm propagation is through offshoots. However, various limitation such as very slow growth, less number of offshoots in mother palm trees (Sharma, 1990) and has the risk of contamination of pests and emergence of diseases (Gueye et al, 2009). Therefore, tissue culture technique or in vitro regeneration can be used as an alternative method for date palm mass propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Among indirect embryogenesis processes, callus induction is very difficult because the date palm is a monoecious, perennial woody plant (Gueye et al, 2009). Therefore, need of a suitable and optimized protocol in order to prepare a nutrient medium for date palm callus induction by the researchers, it would be very helpful for large scale date palm propagation.…”
Section: Introductionmentioning
confidence: 99%
“…2). Callus cells proliferated from the peripheral zones of the stem segments and gradually covered the cut surface, suggesting that they originated from vascular parenchyma or cambium cells (Gueye et al 2009b; Fig. 2).…”
Section: Resultsmentioning
confidence: 99%